TINJAUAN ETIKA ATAS PENGAMBILAN KEPUTUSAN AUDITOR BERDASARKAN PENDEKATAN MORAL - Muhd. Nutyatno; Synthia Dewi (Media Riset Akuntansi, Auditing & Informasi, 2001)
The purposes of this study are to find out whether professional auditor has under-stood ethic code values in Accountant Ethic Codes in Indonesia and whether there is correlation between ethic value understandings with decision-making based on moral standard approach.In this study the author uses descriptive and correlational research method. The purpose of descriptive method is to describe facts and the nature of research object systematically, actually and accurately. Whereas the purpose of correla-tional researches to see correlation between independent and dependent variables. The supporting variables used in this research are auditor understands of ethic values (properness, fair and moral value) and auditor's decision making. Primary data gathered from questionnaire, whereas secondary data gathered from literatures, books, reports and other science writing.Based on the result of data analysis, the author concludes the auditors generally are less understood in ethic values as their guidance, thus decision making is not in accondance with the provision of Indonesian Accountant Commission, espe-cially in understanding of accountant ethic codes. In relation to responsible decision-making, the author concludes that there is correlation between ethic values understanding and such decision making. It is affected by properness, fair and moral factors that relate to decision-making.Keywords: ethics, auditor decision, morale